2022
DOI: 10.1111/jth.15617
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the fibrinolytic speed limit with microwheel co‐delivery of tissue plasminogen activator and plasminogen

Abstract: Background:To reestablish blood flow in vessels occluded by clots, tissue plasminogen activator (tPA) can be used; however, its efficacy is limited by transport to and into a clot and by the depletion of its substrate, plasminogen. Objectives:To overcome these rate limitations, a platform was designed to co-deliver tPA and plasminogen based on microwheels (µwheels), wheel-like assemblies of superparamagnetic colloidal beads that roll along surfaces at high speeds. Methods:The biochemical speed limit was determ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Taking the tissue plasminogen activator (tPA) as an example, its transport mode in occluded vessels with low or no blood flow is diffusion‐dominated, which greatly hinders its transport to the clot site. [ 54 ] Second, the half‐life of tPA‐derived rtPA in the blood is only a few minutes due to rapid receptor‐mediated endocytosis in the liver; so, the drug is usually eliminated before reaching the clot. [ 55 ] All of these greatly limit the therapeutic efficacy of fibrinolytic in arteriovenous thrombolysis.…”
Section: Existing Thrombosis Treatment Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the tissue plasminogen activator (tPA) as an example, its transport mode in occluded vessels with low or no blood flow is diffusion‐dominated, which greatly hinders its transport to the clot site. [ 54 ] Second, the half‐life of tPA‐derived rtPA in the blood is only a few minutes due to rapid receptor‐mediated endocytosis in the liver; so, the drug is usually eliminated before reaching the clot. [ 55 ] All of these greatly limit the therapeutic efficacy of fibrinolytic in arteriovenous thrombolysis.…”
Section: Existing Thrombosis Treatment Techniquesmentioning
confidence: 99%
“…The fibrinolysis rate of drug is limited by both transport processes and biochemical reactions. [54] Moreover, even if drugs are directly injected into the thrombus by intraarterial thrombolysis to improve the enrichment rate, or ultrasound mechanical thrombolysis is used to avoid the loss of delivery process, drugs or microbubbles often stay on the surface of the thrombus, making it difficult to penetrate; so, the efficiency of thrombolysis is still limited. [72,73] 3) The occurrence of side effects such as bleeding.…”
Section: Necessity and Significance Of Nanotechnology Interventionmentioning
confidence: 99%
“…23−25 Microbots designed to release a controlled amount of therapeutic often only do so over a period of hours rather than days due to payload limitations, which is suboptimal for treating chronic illness like IBD. 26 In previous work, we have shown that magnetic microwheels (μ-wheels), disk-like assemblies of superparamagnetic polystyrene microparticles, can translate at speeds of hundreds of μm/s along surfaces when driven by 1−10 mT rotating magnetic fields, 27−29 deliver therapeutic proteins, 30,31 and behave like swarms through complex vessels. 32 To build upon that work, we sought to create magnetically manipulated hydrogel-based milliwheels (m-wheels) designed for translation along mucosal tissues and controlled release of therapeutic proteins with swarm-like behavior.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Wang et al designed an electromagnetically actuated microrobot (EAM) as a mobile micromixer that can be moved to the targeted position in a start-shaped microfluidic chip and controlled to produce rotary motion, which helps in achieving considerable mixing enhancement 49 . In the field of clinical medicine, the microrobots were designed as several small microrods 24 , 50 , microswarm 51 , and microwheel 52 propelled by EMA that are employed to accelerate the t-PA by enhancing the convection induced by local vortex generation. Furthermore, to achieve localization mixing, several additional structures of high magnetic permeability, such as iron nails 24 and magnetic spacer 53 , are added in the microfluidic channel which help locate the microrobot at a targeted position.…”
Section: Introductionmentioning
confidence: 99%